Clinical and laboratory profile of primary hyperparathyroidism in India. Issue 987 (29th January 2008) - Priya, G; Jyotsna, V P; Gupta, N; Chumber, S; Bal, C S; Karak, A K; Seth, A; Ammini, A C
Abstract : Aim: To assess 25-hydroxyvitamin D (25OHD) concentrations in patients with primary hyperparathyroidism and to study the relationship, if any, between vitamin D concentration and bone disease. Methods: Consecutive patients with diagnosed primary hyperparathyroidism were enrolled in the study. Clinical and biochemical details, including serum calcium, phosphate, alkaline phosphatase, parathyroid hormone (PTH) and 25OHD levels, were recorded. An abbreviated skeletal survey and preoperative localisation with ultrasound/CT scan of the neck and tetrofosmin/technetium-99m hexakis(2-methoxyisobutylisonitrile) parathyroid scan was performed. Results: 39 patients with primary hyperparathyroidism were identified (mean (SD) age 38.4 (15.0) years (range 12–72)). The most common presenting features were bone pain (80%), fatigue (80%) and proximal muscle weakness (78%). Brown tumours were present in 58% of cases, renal calculi in 42% and nephrocalcinosis in 12%. The mean (SD) corrected serum calcium concentration was 12.47 (1.58) mg/dl (3.2 (0.4) mmol/l). Serum 25OHD concentration was <5 ng/ml in 11 patients (28%), 5–10 ng/ml in nine (23%), 10–20 ng/ml in 14 (36%), and >20 ng/ml in five (13%). Serum alkaline phosphatase, PTH and gland weight were higher, whereas serum 25OHD was lower, in patients with skeletal disease. Patients with 25OHD concentrations ⩽10 ng/ml had higher body mass index, lower postoperative calcium and higher postoperative PTH. There was a significant correlation between serum calcium and adenoma weight. Conclusion: The profile of patients with diagnosed primary hyperparathyroidism does not seem to have changed over the last decade. Parathyroid gland weight was found to correlate with serum calcium and PTH.